كارطوغرافية أشكال التعرية المائية بحوض واد محاصر الأطلس الكبير الأوسط (المغرب) - السنبري, عبد اللطيف; شطار, الحسين (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة الى كارطوغرافية أشكال التعرية المائية وتوزيعها المجالي بحوض واد محاصر، ولإنجاز ذلك اشتغلنا على التقييم النوعي للتعرية المائية من خلال تحديد مختلف أشكال التعرية وتوزيعها المجالي داخل الحوض بالإعتماد على صور الأقمار الاصطناعية ,والزيارات الميدانية . أظهرت النتائج المحصل عليها ان المجالات التي تنشط بها التعرية الضعيفة تمثل 36% من مساحة الحوض و هي كل المجالات المحمية من طرف الغطاء النباتي الكثيف كما، اما التعرية الغشائية المرتبطة بكشط التربة والسيلان المنتشر تمثل 16 % من مساحة الحوض، تتوزع بشكل متباين جلها يتواجد بالمنطقة السفلى والعليا من الحوض، رغم انها اقل انواع التعرية خطورة على السطح الا انها تؤدي الى افقار المسكات العليا للتربة . اما التخديد بمختلف انواعه يلعب دور مهم في دينامية التعرية، حيث يعمل على تغير الشكل المورفولوجي للسفوح داخل الحوض. The objective of this study is the mapping of erosion forms in the Oued Mhasser watershed. Based on the analysis of Satellite images and the field work for determine the types of erosion. The results obtained shows that slightly eroded zones represent 36% of the total area of the watershed, and all these areas are protected by dense vegetation, whereas sheet and rill erosion represent respectively 16%. Distributed differently, most of them are located in the downstream and upper stream of the basin. However, for the various types of gully, it plays an important role in the dynamics of erosion, this type of erosion is highly visible and affects soil productivity, restricts land use, as it changes the morphological shape of the slopes inside the basin. These results will provide land use planners baseline for land use and risk management.
Cartography of erosion forms in the Oued Mhasser watershed high atlas central (Morocco)
مقال
Keywords: أشكال التعرية ; واد محاصر ; الأطلس الكبير الأوسط